STUDY OF JORDANIAN JOJOBA (SIMMONDSIA CHINENSIS) LIQUID WAX BY GC AND GC/MS - AL-Qizwini, Hani; AL-Khateeb, Ekbal; Mhaidat, Nizar M. (European Scientific Journal, ESJ, 2014)
Context: The oil of Simmondsia chinensis (Link) C.K. Schneid (Simmondsiaceae) has been traditionally used in ethno-medicine because of its unique chemical constituents. Objective: This study determined the Jordanian Jojoba oil components. Fatty acids and sterols profiles were determined by using gas chromatography (GC), while tocopherols profile was determined by using gas chromatography-mass spectrometry (GC/MS). Materials and methods: Jojoba seeds were subjected for hot extraction by solvent (hexane) in addition to cold pressing extraction. Results: The fatty acid α-linolenic acid was in higher percentages within the Jordanian oil than those of Jojoba oil found in other parts of the world. On the other hand, the fatty acids palmitic acid, oleic acid, vaccenic acid, and gondoic acid were in lower percentages within the Jordanian oil. The avenasterol was in higher percentages within the Jordanian oil and the Jordanian Jojoba oil does not contain campesterol or campestanol. In addition, this study found that the major sterols and stanols constituents of the Jordanian Jojoba oil are: sitosterol, campesterol, stigmasterol, cholesterol, avenasterol, and brassicasterol. It was also found that Jojoba oil (hexane extract) contains stigmastadienol while Jojoba oil (cold pressing extract) does not. Jojoba oil (cold pressing extract) contains stigmastenol while Jojoba oil (hexane extract) does not. This study showed that the Jordanian Jojoba oil contains α-tocopherol similar to those of Jojoba oil from around the world. Discussion and conclusion: This is a pioneer results regarding Jojoba which is cultivated in Jordan under different environmental conditions.